Comparison of donor scores in bilateral lung transplantation—A large single‐center analysis. Issue 6 (13th December 2020) - Schwarz, Stefan; Rahimi, Nina; Kifjak, Daria; Muckenhuber, Moritz; Watzenböck, Martin; Benazzo, Alberto; Jaksch, Peter; Knapp, Sylvia; Klepetko, Walter; Hoetzenecker, Konrad; ,
Abstract : Objectifying donor lung quality is difficult and currently there is no consensus. Several donor scoring systems have been proposed in recent years. They all lack large‐scale external validation and widespread acceptance. A retrospective evaluation of 2201 donor lungs offered to the lung transplant program at the Medical University of Vienna between January 2010 and June 2018 was performed. Five different lung donor scores were calculated for each offer (Oto, ET, MALT, UMN‐DLQI, and ODSS). Prediction of organ utilization, 1‐year graft survival, and long‐term outcome were analyzed for each score. 1049 organs were rejected at the initial offer (group I), 209 lungs declined after procurement (group II), and 841 lungs accepted and transplanted (group III). The Oto score was superior in predicting acceptance of the initial offer (AUC: 0.795; CI: 0.776–0.815) and actual donor utilization (AUC: 0.660; CI: 0.618–0.701). Prediction of 1‐year graft survival was best using the MALT score, Oto score, and UMN‐DLQI. Stratification of early outcome by MALT was significant for length of mechanical ventilation (LMV), PGD3 rates, ICU stay and hospital stay, and in‐hospital‐mortality, respectively. To the best of our knowledge, this study is the largest validation analysis comparing currently available donor scores. The Oto score was superior in predicting organ utilization, and MALT score and UMN‐DLQI for predicting outcome after lung transplantation. Abstract : In this large retrospective analysis, the authors compare several available donor scores and their utility in predicting lung offer acceptance, lung utilization, and postoperative outcomes.